Kidney function in rice workers exposed to heat and dehydration in Costa Rica - Crowe, Jennifer (2022)
This study received funding from the National University of Costa Rica’s Institutional Fund for Academic Development (FIDA) program (communication number CONSACA-009-2015) and was approved by the Institutional Ethical Review Board (CECUNA) of the National University in Costa Rica. This article belongs to the Special Issue Prevention of Adverse Health Outcomes Related to Heat Exposure in Working Populations